2015
DOI: 10.1016/j.ultsonch.2015.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive experimental and numerical investigations of the effect of frequency and acoustic intensity on the sonolytic degradation of naphthol blue black in water

Abstract: In the present work, comprehensive experimental and numerical investigations of the effects of frequency and acoustic intensity on the sonochemical degradation of naphthol blue black (NBB) in water have been carried out. The experiments have been examined at three frequencies (585, 860 and 1140 kHz) and over a wide range of acoustic intensities. The observed experimental results have been discussed using a more realistic approach that combines the single bubble sonochemistry and the number of active bubbles. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 55 publications
1
18
0
Order By: Relevance
“…The sonochemical removal of 20 mg/L AO7 was conducted at different input powers of 40, 60, 80, 100 and 120 W and the results are presented in Figure 7. It is clear that the removal efficiency increased significantly with an increase of the applied power from 40 to 120 W. These finding are in line with those of Villaroel et al (2014), Quesada-Pe˜nate et al (2009) andFerkous et al (2015b) that suggested higher degradation rates of various pollutants at higher supplied powers.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The sonochemical removal of 20 mg/L AO7 was conducted at different input powers of 40, 60, 80, 100 and 120 W and the results are presented in Figure 7. It is clear that the removal efficiency increased significantly with an increase of the applied power from 40 to 120 W. These finding are in line with those of Villaroel et al (2014), Quesada-Pe˜nate et al (2009) andFerkous et al (2015b) that suggested higher degradation rates of various pollutants at higher supplied powers.…”
Section: Resultssupporting
confidence: 88%
“…Since higher production of radicals could be achieved under higher power (Ferkous et al, 2015b;Merouani et al, 2010b), more AO7 was degraded during the same sonication time. After 90 min, more than 71% of the dye remained in the solution at 40 W. However, the remained fraction decreased considerably to 40, 13, 8 and 0% with the power increase from 40 to 60, 80, 100 and 120 W, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…2. As seen from this figure, sonication alone degraded efficiently NBB, which is mainly due to the • OH radical attack at the bubble/solution interface, as demonstrated early [48,49]. It should also be mentioned that previous efforts have demonstrated that the degradation rate of NBB cannot be associated with a first-order law [48].…”
Section: Sonolytic Degradation Of Nbb In the Presence Of Psmentioning
confidence: 60%
“…We note here that there are other nitrogen‐containing radicals, i.e. NO 2 • , NO 3 • , as well as reactive atoms such as N that are formed in the case of air bubble . However, their estimated amounts were very low as compared with that of • OH, which is mainly due to the fact that such radicals reacts quickly to form nitrous and nitric acids (HNO 2 and HNO 3 ) as final products of air sonolysis inside the bubble .…”
Section: Resultsmentioning
confidence: 82%